Deciphering the Role of Developing Brain Homeobox Genes During Zebrafish Retina Regeneration - Karande, Kranti Yuvaraj (IISER M, 2015)
In contrast to mammals, Zebra fish shows complete retinal regeneration in response to injury. Muller Glia cells play a very critical role in the process of Retina regeneration in Zebra fish. Process of retinal regeneration gets completed in three stages: Dedifferentiation, Proliferation, and Re differentiation. Here I report that, Developing Brain Homeobox Genes are robustly expressed in Ganglion cell layer, Horizontal cells in INL and Muller Glia of regenerating retina also, playing a role in the process of regeneration. I also report that, dbx expression might be regulated by Wnt-β catenin signalling pathway.
Keywords: Biology; Retina; Genes; Zebra fish